Study on a horizontal axial flow pump during runaway process with bidirectional operating conditions - Kan Kan (Nature Portfolio, 2021)
Abstract The ultra-low head pump stations often have bidirectional demand of water delivery, so there is a risk of runaway accident occurring in both conditions. To analyze the difference of the runaway process under forward runaway condition (FRC) and backward runaway condition (BRC), the whole flow system of a horizontal axial flow pump is considered. The Shear-Stress Transport (SST) k–ω model is adopted and the volume of fluid (VOF) model is applied to simulate the water surface in the reservoirs. Meanwhile, the torque balance equation is introduced to obtain the real time rotational speed, then the bidirectional runaway process of the pump with the same head is simulated. In addition, the vortex transport equation and swirl number are proposed to reveal the flow characteristics during the runaway process. The results show that the runaway process can be divided into five stages: the drop, braking, rising, convergence and runaway stages, according to the changing law of torque curve. In the rising stage, the pressure difference on the blade surface continues to increase, which contributes to the abnormal torque increase. In this stage, the flow hits the pressure surface (PS) at a faster speed enlarging the pressure on PS, and the flow separation takes place on the suction surface (SS) weakening the pressure on SS. During the convergence and runaway stage, the pulsation amplitude of torque and axial force under FRC is obviously larger than those under BRC. This is because the rotation frequency of the vortex rope is the same as main pressure fluctuation frequency in impeller under FRC, which enhances the pulsation amplitude. Whereas the vortices are broken due to the inhibitive effect from guide vanes under BRC.